Anti-cancer immune responses to DNA damage response inhibitors: Molecular mechanisms and progress toward clinical translation - Carlsen, Lindsey; El-Deiry, Wafik S. (Frontiers in Oncology, 2022)
DNA damage response inhibitors are widely used anti-cancer agents that have potent activity against tumor cells with deficiencies in various DNA damage response proteins such as BRCA1/2. Inhibition of other proteins in this pathway including PARP, DNA-PK, WEE1, CHK1/2, ATR, and ATM can sensitize cancer cells to radiotherapy and chemotherapy, and such combinations are currently being tested in clinical trials for treatment of many malignancies including breast, ovarian, rectal, and lung cancer. Unrepaired DNA damage induced by DNA damage response inhibitors alone or in combination with radio- or chemotherapy has a direct cytotoxic effect on cancer cells and can also engage anti-cancer innate and adaptive immune responses. DNA damage-induced immune stimulation occurs by a variety of mechanisms including by the cGAS/STING pathway, STAT1 and downstream TRAIL pathway activation, and direct immune cell activation. Whether or not the relative contribution of these mechanisms varies after treatment with different DNA damage response inhibitors or across cancers with different genetic aberrations in DNA damage response enzymes is not well-characterized, limiting the design of optimal combinations with radio- and chemotherapy. Here, we review how the inhibition of key DNA damage response enzymes including PARP, DNA-PK, WEE1, and CHK1/2, ATR, and ATM induces innate and adaptive immune responses alone or in combination with radiotherapy, chemotherapy, and/or immunotherapy. We also discuss current progress in the clinical translation of immunostimulatory DNA-damaging treatment regimens and necessary future directions to optimize the immune-sensitizing potential of DNA damage response inhibitors.